The effect of vagus nerve stimulation on heart rate and respiration rate and their impact on seizure susceptibility in anaesthetized rats under pentylenetetrazol - Chávez Cerda, Javier; Acedo Reina, Elena; Dereli, Ayse S.; Vande Perre, Louis; Raffoul, Romain; Verstraeten, Maxime; Ngan Yamb, Michel-Antony; Germany Morrison, Enrique; Collard, Elise; Apaire, Auriane; Doguet, Pascal; Garnier, Jérôme; et al. (Frontiers in Neuroscience, 2025)
Despite the proven efficacy of vagus nerve stimulation (VNS) in seizure control, its precise mechanism of action remains unclear. VNS is known to impact the cardiorespiratory system. In this study, we explored the effects of standard and breathing-synchronized VNS on heart and respiratory rates in anesthetized epileptic rats, as well as their impact on seizure susceptibility. Seizures were induced in rats by intravenous pentylenetetrazol (PTZ) infusion. Three animal groups (n = 4) were subjected to different types of stimulation: Sham VNS, Standard VNS, and Breathing-Synchronized VNS. Measurements included respiration, electrocardiogram, electroencephalogram, and vagal electroneurogram. Each experiment began with a 5-min baseline period, followed by PTZ infusion until tonic–clonic seizure onset, confirmed by video recording and electroencephalogram. Results indicate that the stimulation significantly decreased the heart rate below baseline levels for standard VNS (−120.0 ± 69.1 bpm) and breathing-synchronized VNS (−84.9 ± 61.0 bpm), overcoming the heart rate increasing effect of PTZ infusion observed in the sham VNS (+79.2 ± 35.5 bpm), and there was no recovery during OFF periods. Regarding the breathing rate changes, the sham VNS group presented a slight increase with respect to baseline (+13.6 ± 1.8 bpm). The stimulation slightly increased the average breathing rate for standard VNS (+13.0 ± 14.6 bpm) and breathing-synchronized VNS (+13.7 ± 10.4 bpm), however with significantly enlarged standard deviation. More specifically, the breathing rate presented a pattern that suggests that the rats experienced respiratory hypoxia under stimulation. The VNS modulation of the heart rate and breathing rate in the standard VNS group was similar in the breathing-synchronized VNS, suggesting that the VNS effect is cumulative. Unexpectedly, the sham VNS group required a higher PTZ dose (79.7 ± 13.4 mg/kg) to reach tonic–clonic seizures compared to the standard VNS group (57.9 ± 9.8 mg/kg), and the breathing-synchronized VNS group (60.0 ± 8.7 mg/kg), pointing to an increased seizure susceptibility of VNS in this particular model. Additionally, the latency of the seizures was longer in the sham VNS (291.5 ± 84.4 s) compared to standard VNS (200.5 ± 59.5 s) and breathing-synchronized VNS (206.9 ± 66.0 s), meaning that the seizures under stimulation were starting earlier. A significant linear relationship was found between heart rate and respiratory rate changes, and seizure susceptibility (R2 = 0.62, p-value = 0.012). We hypothesize that the significant drop in heart rate and the presence of altered respiration patterns, such as apneas or changes in breathing rates, caused by VNS, are related to hypoxia and hypotension conditions, which could increase susceptibility to PTZ. Future investigations with larger sample sizes, incorporating blood pressure and oxygen saturation monitoring, are needed to sort out the role of hypoxia and hypotension as potential covariates affecting the seizure susceptibility caused by overstimulation. Such a finding would support the idea that VNS safety and efficacy require precise adjustments.